Pengaruh Penggunaan Tik Tok Terhadap Minat Belajar Siswa pada Mata Pelajaran PAI di SMPN 3 Payakumbuh (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research is motivated by a decrease in interest in learning caused by one of the reasons for using Tik Tok. This research aims to determine the level of use of Tik Tok at SMPN 3 Payakumbuh, determine students' interest in learning in PAI subjects at SMPN 3 Payakumbuh and determine the influence of the level of use of Tik Tok on students interest in PAI subjects at SMPN 3 Payakumbuh. This research uses a quantitative correlational approach with a population of 817 students and a sample of 89 students using simple random sampling techniques. The respondents data were analysed using SPSS version 25. The research results showed descriptive tests of Tik Tok use with many indicators and interest in learning with indicators in the medium category. There is a significant influence from the use of Tik Tok on students interest in PAI subjects. This is proven by the strong relevantion between the variable use of Tik Tok and interest in understanding with a correlation value of 0.624 and a significance value of 0.00
Keywords: Tik Tok used; Interest in learning; SMPN 3 Payakumbuh